Letter from Carl D. Duncan to Patricia Whiting, January 11, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan enthusiastically recalls attending a film on wildlife of Alaska, and decribes dinner with his colleagues.